Standardizing course assessment in competency-based higher education: an experience report - Vargas, Hector; Arredondo, Emanuel; Heradio, Ruben; Torre, Luis de la (Frontiers in Education, 2025)
IntroductionCompetency-Based Education (CBE) has become increasingly important in Chilean higher education since the 2006 reform, which aimed to improve educational quality. However, implementing CBE effectively poses challenges, particularly in developing assessments that adhere to CBE principles and are consistent across all university courses. To address this issue, the Competency Assessment and Monitoring (C-A&M) model was created. This study evaluates the effectiveness of C-A&M in standardizing course assessments within the CBE paradigm at the Pontifical Catholic University of Valparaíso (PUCV) in Chile.MethodsTwo observational studies were conducted. The first study utilized a within-group design and included 20 Engineering courses. The second study employed a between-groups design, examining the perceptions of 109 instructors from various faculties, including Law, Economic and Administrative Sciences, Philosophy, and Education, among others.ResultsThe within-group study emphasized the need for better course assessment and alignment of learning objectives with competencies. It found a positive correlation between C-A&M and the effective implementation of CBE in university courses. The between-groups study showed a minor effect size but suggested a similar relationship.DiscussionAssessment based on CBE principles is not being effectively implemented at PUCV. Key areas for improvement include the evaluation plan, aligning learning objectives with competencies, and coordinating training with these objectives. The application of C-A&M has led to significant improvements, indicating a positive correlation between its use and these enhancements.